Auxiliary selection across Catalan dialects: an overview - Pineda, Anna; Salvà, Sebastià; Cremades, Elga (Borealis – An International Journal of Hispanic Linguistics, 2024)
This article presents a comprehensive description of auxiliary selection in Catalan. Specifically, after explaining how the phenomenon worked in Old Catalan, we show what are the factors (such as the event/argument structure or the grammatical person, among others) that determine the use of be and have in those Catalan varieties ​​that, although with some innovations, retain this distinction: (i) Algherese Catalan, (ii) Northern Catalan and some varieties of Central Catalan, (iii) Ribagorçan Catalan, and (iv) Balearic Catalan. Likewise, we show a series of theoretical considerations that we believe relevant for the analysis of the patterns of variation found in Catalan and, by extension, in Romance.